Feasibility Evaluation of CAM Milling Learning Materials Based on Project-Based Learning Assisted by Inventor CAM Ultimate: A Study of Validity and Practicality - Elfahmi Dwi Kurniawan; Nopriyanti Nopriyanti; Rudi Hermawan; Ari Saputra; Prandika Dafatriz Arta; Rangga Satria Suprayogo; Putri Indah Yanti (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study aims to develop valid and practical CAM Milling instructional materials based on Project-Based Learning (PjBL) and assisted by Inventor CAM Ultimate for the Advanced CAM course. Using the 4D development model—Define, Design, Develop, and Disseminate—the materials were designed to address the lack of CAM-focused resources and provide project-oriented learning experiences. Validation by material and media experts resulted in average scores of 4.29 and 4.56, categorized as very valid. Field trials involving 20 students produced a practicality score of 4.33, indicating very practical use. These results confirm that the developed instructional materials meet the criteria of validity and practicality, making them suitable for mechanical engineering education